Participatory Moral Reasons: Their Scope and Strength - Garrett Cullity (Journal of Practical Ethics)
A familiar part of ordinary moral thought is this idea: when other people are doing something worthwhile together, there is a reason for you to join in on the same terms as them. Morality does not tell you that you must always do this; but it exerts some pressure on you to join in. Suppose we take this idea seriously: just how should it be developed and applied? More particularly, just which groups and which actions are the ones with respect to which you have participatory moral reasons? And just when is it wrong not to join in? I present answers to these questions, and discuss the implications—including for joint action on a very large scale, like global efforts to address climate change or fight a pandemic.